2019
DOI: 10.1590/s1677-5538.ibju.2018.0808
|View full text |Cite
|
Sign up to set email alerts
|

Novel homozygous mutation in a colombian patient with persistent müllerian duct syndrome: expanded phenotype

Abstract: The anti-Müllerian hormone triggers the regression of uterus and fallopian tubes in male embryos; if there are problems in the synthesis or action of this protein, Müllerian structures persist in an otherwise phenotypic male. The most frequent clinical presentation of Persistent Mullerian Duct syndrome is cryptorchidism and inguinal hernia. The few cases reported in adults are incidental findings or inguinal hernias. However, we present an adult male with history of bilateral cryptorchidism with unsuccessful o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Adding with our patients in China, there were 93 families with 78 different variants in AMH ( Supplementary Table 2 ) and 94 families with 80 different variants in AMHR2 have been reported ( Supplementary Table 3 ). 6 8 9 10 11 12 13 14 15 16 The relationship between the phenotypes and genotype of all patients was analyzed statistically ( ). There was no significant difference in anatomy between patients with either AMH or AMHR2 variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding with our patients in China, there were 93 families with 78 different variants in AMH ( Supplementary Table 2 ) and 94 families with 80 different variants in AMHR2 have been reported ( Supplementary Table 3 ). 6 8 9 10 11 12 13 14 15 16 The relationship between the phenotypes and genotype of all patients was analyzed statistically ( ). There was no significant difference in anatomy between patients with either AMH or AMHR2 variants.…”
Section: Resultsmentioning
confidence: 99%
“…In our literature review, variants of AMH and AMHR2 were reported in 87.9% of all patients and were approximately equally distributed among the genes coding AMH and its type II receptor, AMHR2 . 6 8 9 10 11 12 13 14 15 16 Statistics indicated that AMH presented 78 different variants in 93 families, and 80 different alleles of AMHR2 were discovered in 94 families. In our Chinese patients, mutational analyses revealed possible causative variants in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, el paciente (caso 10) con síndrome del conducto mülleriano persistente (SCMP) fue diagnosticado a los 33 años por hallazgo incidental intraoperatorio de derivados de los conductos de Müller, cirugía motivada por masa tumoral (seminoma). Tenía antecedente de criptorquidia bilateral con orquidopexia fallida e historia de infertilidad(22). Se destaca que la incidencia de transformación maligna en SCMP es 18%, similar a la tasa de incidencia de transformación maligna en la criptorquidia en hombres normales, siendo el seminoma el tumor más frecuente en pacientes con SCMP(22,23).En relación con el grupo de TDS 46,XX, se destacan tres subgrupos de acuerdo con la etiología: 1) Trastornos del desarrollo gonadal, 2)Trastornos asociados a exceso de andrógenos y 3) otros en los que se incluye extrofia de cloaca, atresia vaginal, entre otros síndromes.…”
unclassified
“…ciplinary team must intervene to confirm the diagnosis immediately at birth. DSD can also appear during childhood, associated with other syndromic characteristics; during adolescence due to virilization, absence of puberty, or primary amenorrhea; and during adulthood, associated with infertility, gonadal tumors, and other complications (6,9,23). Regardless of the specific needs of each of those groups, a timely multidisciplinary team intervention is always recommended.The results presented herein show us the importance of cytogenetic analyses in the diagnosis of DSD.…”
mentioning
confidence: 99%
“…1-12.Mon. : Months, M: male, F: female, RG: right gonad, LG: left gonad * These patients were included in García-Acero et al(23) as part of the recorded medical histories of the patients with chromosomal alterations, analyzed at our institution.…”
mentioning
confidence: 99%